2017
DOI: 10.1007/s00526-017-1206-9
|View full text |Cite
|
Sign up to set email alerts
|

A sharp bound on the Hausdorff dimension of the singular set of a uniform measure

Abstract: The study of the geometry of n-uniform measures in R d has been an important question in many fields of analysis since Preiss' seminal proof of the rectifiability of measures with positive and finite density. The classification of uniform measures remains an open question to this day. In fact there is only one known example of a non-trivial uniform measure, namely 3-Hausdorff measure restricted to the Kowalski-Preiss cone. Using this cone one can construct an n-uniform measure whose singular set has Hausdorff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For an in-depth introduction, we refer the reader to the exposition of Preiss' theorem by De Lellis [17]. The classi cation of m-uniform measures in R n is as of yet incomplete, but some progress has recently been made by Tolsa [59] and Nimer [47,48]. The deep connections between the existence of densities and recti ability of sets and absolutely continuous measures in Euclidean space, as described above, have been explored in metric spaces beyond R n by several authors; see e.g.…”
Section: Hausdor Densities and Recti Abilitymentioning
confidence: 99%
“…For an in-depth introduction, we refer the reader to the exposition of Preiss' theorem by De Lellis [17]. The classi cation of m-uniform measures in R n is as of yet incomplete, but some progress has recently been made by Tolsa [59] and Nimer [47,48]. The deep connections between the existence of densities and recti ability of sets and absolutely continuous measures in Euclidean space, as described above, have been explored in metric spaces beyond R n by several authors; see e.g.…”
Section: Hausdor Densities and Recti Abilitymentioning
confidence: 99%
“…Recently Nimer [Nim18] produced many interesting examples. See also [Tol15a], [Nim17] and [Nim19] for other results.…”
Section: Tangent Planesmentioning
confidence: 92%
“…The first example is due to Kowalski and Preiss [14], who showed that the measure H 3 Σ is a 3-flat measure in R 4 , where Σ = {(x 1 , x 2 , x 3 , x 4 ) ∈ R 4 : x 2 1 = x 2 2 + x 2 3 + x 2 4 } is the light cone. In fact, Kowalski and Preiss have completely classified (n − 1)-uniform measures in R n for all values of n: every such measure is either (n−1)-flat or is proportional to H n−1 M where M is an (n − 1)-dimensional algebraic variety in R n which is isometric to Σ × R n n − 1 remains unknown, although recent work of Nimer [24], [25], [26] has improved our understanding and provided new examples. Kirchheim and Preiss [13] proved that the support of a uniform measure in R n is an analytic variety, and Tolsa [29] showed that such supports satisfy the David-Semmes 'weak constant density' condition and hence are uniformly rectifiable.…”
Section: Introductionmentioning
confidence: 99%